ความสัมพันธ์ระหว่างประสบการณ์การปฏิบัติงาน การอบรมเฉพาะทาง ความฉลาดทางอารมณ์ สภาพแวดล้อมในการทำงาน กับสมรรถนะพยาบาลวิชาชีพในหอผู้ป่วยวิกฤตศัลยศาสตร์หัวใจและทรวงอก โรงพยาบาลระดับตติยภูมิ - นฤมล ศิลวิศาล (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
The purposes of this study were to study nurse competency, emotional intelligence, working environment in cardiothoracic surgical ward, to examine the relationships between working experiences, educational training, emotional intelligence, working environment and nurse competency in cardiothoracic surgical ward, and to search for the variables which could predict nurse competency in cardiothoracic surgical ward. The samples consisted of 125 of professional nurse in cardiothoracic surgical ward. An instrument as developed by researcher, judged by the panel of experts which has been tasted for content validity and Cronbach alpha coffcient of reliability were .96 .96 and .97. The data were analyzed by using mean, standard deviation, Chi-square, Pearson’s product moment correlation coefficient and stepwise multiple regression analysis. The results were as follows : Nurse competency in cardiothoracic surgical ward, emotional intelligence and working environment was at high level (mean = 4.23, 4.01 and 4.17, respectively). Working experiences, educational training, emotional intelligence and working environment were significantly related to nurse competency in cardiothoracic surgical ward, at .05 level (r =.368, .315 .631 and .593, respectively). Factor significantly predicted Nurse competency in cardiothoracic surgical ward were working environment, emotional intelligence and working experiences at .05 level. These predictors were accounted for 53.3 percent (R2= .533). The standardized equation was as follow: Z nurse competency in cardiothoracic surgical ward = .350 Z* working environment +.329 Z* emotional intelligence+.320 Z* working Experiences